How do economic growth, trade openness, and non-renewable and renewable energy affect environmental quality in VISTA Countries? - Bayar, İlyas; Dabakoglu, Mehmet (Universitas Islam Indonesia, 2024)
Purpose ─ This study examines the effects of economic growth, the use of renewable and non-renewable energy sources, and trade openness on carbon emissions in VISTA countries (Vietnam, Indonesia, South Africa, Turkiye, and Argentina)Method ─ In this work, empirical methods include the second-generation unit root and cointegration tests, as well as Panel AMG and Panel CCE estimators.Findings ─ The following are the key findings. First, the variables demonstrate a long-run relationship. Second, economic growth and the consumption of non-renewable energy sources contribute to an increase in carbon emissions over time, whereas the consumption of renewable energy sources lowers carbon emissions over time. Implication ─ To promote sustainable growth in VISTA countries, it is recommended to increase investments in renewable energy sources while enhanching public sector supports for the private sector.Originality ─ This is the first study to examine how economic growth, trade openness, and renewable and non-renewable energy sources affect carbon emissions in VISTA nations.